Improved single phase modeling of propylene polymerization in a fluidized bed reactor - Shamiri, A.; Hussain, Mohd Azlan; Mjalli, F.S.; Mostoufi, N. (Computers & Chemical Engineering, 2012)
An improved model for the production of polypropylene in a gas phase fluidized bed reactor was developed. Comparative simulation studies were carried out using the well-mixed, constant bubble size and the improved models. The improved model showed different prediction characteristics of polymer production rate as well as heat and mass transfer behavior as compared to other published models. All the three models showed similar dynamic behavior at the startup conditions but the improved model predicted a narrower safe operation window. Furthermore, the safe ranges of variation of the main operating parameters such as catalyst feed rate and superficial gas velocity calculated by the improved and well mixed models are wider than that obtained by the constant bubble size model. The improved model predicts the monomer conversion per pass through the bed which varies from 0.28 to 5.57% within the practical ranges of superficial gas velocity and catalyst feed rate.